MATHEMATICAL MODELING OF REGULAR VORTICAL STRUCTURES IN THE ANGULAR STREAMLINED CONFIGURATIONS SURFACES. - Шквар, Є. (Science-based technologies, 2011)
The effective numerical method for three-dimensional turbulent flow along an edge of a streamwise corner is elaborated. The hybrid algebraically-differential model of turbulent viscosity has been adopted to the given problem. Presented results have demonstrated reproduction in calculations the governing characteristics of main and secondary vortical flows and can be effectively implemented in different energetic equipment and high-speed transport vehicles.